Shifting the mindset—adolescent and young adult rheumatology in transition. (April 2020) - Willis, Emily; McDonagh, Janet E
Summary: Almost 30 years have passed since publication of the first reports acknowledging the crucial importance of transitional care for adolescents and young adults with chronic disease, but universal implementation has yet to be achieved. Progress has undoubtedly been made, with increasing evidence for best practice in transitional care. However, translation of research and guidance into clinical practice continues to be challenging. Neuroscience advances in understanding the changes occurring in the adolescent brain demand that the third phase of transition (ie, post-transfer to adult services) is given further attention, with recognition that transfer itself is not the end of the transition process. The complex, often unwieldy health systems delivering care must also be considered. Paediatric and adult rheumatology practitioners need to collaborate not only with each other, but also with practitioners in other disciplines, specialties, and agencies, to plan and commission rheumatology services that are responsive to adolescents and young adults. A shift in approach from focusing on health transition towards developmentally appropriate health care has the potential to improve the care provided during this vulnerable life stage, increasing the likelihood of continuing engagement of patients in their own health care into adulthood and thereby improving health outcomes.